2020
DOI: 10.3889/oamjms.2020.4384
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Factor V Leiden G1691A, Prothrombin G20210A, MTHFC677T Mutations, and Early Recurrent Pregnancy Loss in a Group of Sudanese Women

Abstract: BACKGROUND: Recurrent pregnancy loss is classically defined as the occurrence of three or more consecutive pregnancy loss. Recurrent pregnancy loss affects from 1-5% of the reproductive age couples. This diagnosis is both emotionally challenging and confusing for most couples, as the definitive diagnosis using conventional evaluations is found in fewer than half of the couples experiencing repeated loss. AIM: The purpose of this study was to define the association between Factor V Leiden G1691A, Prothrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
1
4
1
Order By: Relevance
“…It renders FVL resistant to the activated PC, thereby decreasing the anticoagulant function of PC and predisposition to thrombus formation [12]. The prothrombin G20210A mutation of the prothrombin gene exhibits increased synthesis and functional capability of prothrombin, favoring thrombosis In this study, the frequency of the FVL G1691A heterozygous mutation (G/A) was 3.5%, whereas that of the homozygous mutation (A/A) was 0.5% [OR = 17.71, 95% confidence interval (9%% CI): = 1.015-309.05], which is consistent with the results of previous studies [17,18]. The rate of the FVL G1691A polymorphism is almost similar in various pregnancy-associated clinical manifestations [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It renders FVL resistant to the activated PC, thereby decreasing the anticoagulant function of PC and predisposition to thrombus formation [12]. The prothrombin G20210A mutation of the prothrombin gene exhibits increased synthesis and functional capability of prothrombin, favoring thrombosis In this study, the frequency of the FVL G1691A heterozygous mutation (G/A) was 3.5%, whereas that of the homozygous mutation (A/A) was 0.5% [OR = 17.71, 95% confidence interval (9%% CI): = 1.015-309.05], which is consistent with the results of previous studies [17,18]. The rate of the FVL G1691A polymorphism is almost similar in various pregnancy-associated clinical manifestations [19].…”
Section: Discussionsupporting
confidence: 92%
“…However, a recent study did not detect this mutation in a selected group of pregnant women [20]. In another study conducted in Sudan, the prevalence of prothrombin G20210A mutation was reported as 3.0%, which is higher than that observed in this study [17]. Other researchers have also reported a high prevalence of prothrombin G20210A heterozygous mutations in pregnant women with DVT or PE [19].…”
Section: Discussioncontrasting
confidence: 79%
“…FVL can induce activated protein C (APC) resistance, which in turn leads to a hypercoagulable state [ 82 ]. However, the susceptibility of FVL to RPL is controversial, and both strong and negative associations with RPL have been reported [ 83 ], [ 84 ], [ 85 ]. Recently, Eslami et al.…”
Section: Maternal and Paternal Genetic Factors Account For Rplmentioning
confidence: 99%
“…However, some studies reject that association. [4][5][6] Based-on a numerous of systematic reviews and meta-analyses, association of the Prothrombin G20210A mutation with the risk of pregnancy complications is well recognized. 7,8 There are few published data on Prothrombin G20210A and recurrent pregnancy loss among Sudanese.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 There are few published data on Prothrombin G20210A and recurrent pregnancy loss among Sudanese. 6 Thus, current study aimed to estimate the prevalence of the Prothrombin G20210A mutation among Sudanese women with recurrent pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%